PERLINDUNGAN HUKUM TERHADAP USAHA WARNET DALAM PERJANJIAN PEMBERIAN KUOTA INTERNET YANG DIBERIKAN OLEH PROVIDER - Rahmat Ananta, Faizal; M. E. Purwani, Sagung Putri (Kertha Semaya : Journal Ilmu Hukum, 2013)
Legal protection for the parties to an agreement.means to obtain protection in cerrying out the agreement in order to enjoy all the rights granted by law. Agreement shall implement all the right and obligation in accordance whith the agreement. The risk that the consumer received the bad faith or efforts in one agreement is default. This is done outside of the covenant which was made unilaterally.
Keywords: Default, Agreement, Legal Protection